ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL OPEN-ENDED MATERI SPLDV - Salis Rifqotun Nisa; Nida Sri Utami; Rita Pramujiyanti Khotimah (Universitas Bhinneka PGRI, 2025)
The purpose of this study is to provide an in-depth analysis of students critical thinking skills in solving open-ended problems on the material of the system of linear equations of two variables. This type of research uses qualitative methodology. This research begins with giving a test of critical thinking ability of open-ended problem type that have passed declared valid to 20 students of class VIII A SMP Muhammadiyah 6 Surakarta which is the continued with the selection of 3 subjects representing high, medium and low critical thinking ability for the purpose of this study. The data collection techniques used open-ended question tests and interviews. Data were analyzed using critical thinking indicators that include interpretation, analysis, evaluation, and inference. The analysis results show that (1) Subjects with high critical thinking ability are capable of mastering four indicators, which include interpretation, analysis, evaluation, and inference on each problem; (2) Subjects with moderate critical thinking ability are only capable of mastering several indicators in each problem. For question 1, only three indicators are mastered namely analysis, evaluation and inference. In question 2, only two indicators are mastered namely interpretation and evaluation. In question 3, only three indicators are mastered namely interpretation, evaluation and inference; (3) Subjects with low critical thinking ability can only master fewer indicators in each question. In question 1, only one indicator was mastered namely inference. For question 2, only two indicators are mastered namely interpretation and analysis. Whereas in question 3 only one indicator is mastered namely interpretation.